Infection of Chicken Anaemia Virus: Etiology, Epidemiology, Clinical Sign, Pathological Changes and Disease Control - Wahyuwardani, Sutiastuti; Syafriati, Tatty (Indonesian Animal Sciences Society, 2005)
Initially, Chicken anaemia virus (CAV) is known as CAA, which was first isolated by Yuasa in Japan in 1976. CAV particles are non enveloped with a diameter of 19 .1-20 .7nm, belonging to the family Circoviridae, genus Gyrovirus . CAV infection was first appeared in Indonesia at the same time as the outbreak of stunting and runting syndrome in 1996 with a mortality rate of 5-15% but it may reach to 60%. CAV can be transmitted vertically or horizontally. Chicken all ages is susceptible to infection. Infection of CAV occurred in young chicken flock at 2-3 weeks growth of age, causing clinical signs while in old chicken flock which is sub clinical. The signs of infectious of CAV are retarded, anaemia, anorexia, pale of face and pial. The pathology anatomy changes are pale carcases, yellowish bone marrow, atrophy of thymus and bursa fabricius . Whereas, histophatological changes are thymic necrosis of cortex and medulla, lymphocyte depletion of thymus, bursa fabricius and bone marrow. Diagnose of CAV is based on pathological changes and followed by the isolation of certain lymphoblastoid chicken cell MDCC-MSB I and then, is identified by virus neutralization. The presence of virus can also be identified by immunofluorescent and immunoperoxidase staining, in situ hybridization technique or PCR. For antibody detection, ELISA technique can be used. The syndromes of CAV infection are closely associated with those of osteopetrosis, reovirus, infectious bursal disease (IBD) and Marek. Vaccination programme in breeding farm is needed to induce maternal antibody. This paper describes the CAV disease and its occurrence in Indonesia. Key word : Chicken anaemia virus, diagnose, pathology anatomy, histopathology, control